2013
DOI: 10.1371/journal.pone.0071181
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Bearing Locomotion in the Developing Opossum, Monodelphis domestica following Spinal Transection: Remodeling of Neuronal Circuits Caudal to Lesion

Abstract: Complete spinal transection in the mature nervous system is typically followed by minimal axonal repair, extensive motor paralysis and loss of sensory functions caudal to the injury. In contrast, the immature nervous system has greater capacity for repair, a phenomenon sometimes called the infant lesion effect. This study investigates spinal injuries early in development using the marsupial opossum Monodelphis domestica whose young are born very immature, allowing access to developmental stages only accessible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 74 publications
(113 reference statements)
1
15
0
Order By: Relevance
“…The behavioral recovery seen in our initial study using this model was reminiscent of that seen in similar neonatal mammalian models (Saunders et al, ; Wang et al, : Wheaton et al, ), and we showed additionally a parallel neurophysiological recovery involving the re‐establishment and reorganization of synaptic connections (Boulland et al, ). The relevant permissive cellular mechanisms operating in this and other neonatal spinal cord injury models have not been well characterized, however, in contrast to the relatively extensive literature on this point in the adult spinal cord.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The behavioral recovery seen in our initial study using this model was reminiscent of that seen in similar neonatal mammalian models (Saunders et al, ; Wang et al, : Wheaton et al, ), and we showed additionally a parallel neurophysiological recovery involving the re‐establishment and reorganization of synaptic connections (Boulland et al, ). The relevant permissive cellular mechanisms operating in this and other neonatal spinal cord injury models have not been well characterized, however, in contrast to the relatively extensive literature on this point in the adult spinal cord.…”
Section: Introductionsupporting
confidence: 75%
“…Hence, recovery from damage to the spinal cord is likely to be greater in neonatal and young postnatal animals and humans than in adults. Evidence for this in mammals comes from a limited number of studies (Saunders et al, 1995(Saunders et al, , 1998Wang et al, 1998;Wheaton et al, 2011Wheaton et al, , 2013Boulland et al, 2013), including observations in humans (Hadley et al, 1988;Birney and Hanley, 1989;Hamilton and Myles, 1992;Wang et al, 2004). To better understand the difference in pathophysiology and recovery between the injured immature and adult spinal cord, we recently developed a standardized neonatal mouse spinal cord compression injury model (Boulland et al, 2013;Z€ uchner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activities, such as voluntary wheel running, swimming, weight bearing, and treadmill exercise improve activity of neuronal and non-neuronal cell and axonal regrowth after peripheral and central nerve injury ( Cotman et al, 2007 ; Liao et al, 2017 ; Wheaton et al, 2013 ). Previous studies reported that exercise might be a critical mediator to improve functional recovery and pain-related cellular reactions with the cell survival and differentiation in the injured area ( Fouad et al, 2000 ; Sumizono et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This makes the swim test a good test to detect the effects of locomotion in the absence of this reflex input, and a good measure of supraspinal control ( Saunders et al , 1998; Smith et al , 2006; Magnuson et al , 2009; Wheaton et al , 2011; Wheaton et al , 2013). …”
Section: Discussionmentioning
confidence: 99%